Endotherapy in Pancreatic Diseases - Jearth, Vaneet; Rana, Surinder S. (Journal of Digestive Endoscopy, 2022)
Interventional endoscopy is now considered an effective minimally invasive treatment modality for the management of pancreatic diseases. It is important for the clinician to know the indications and contraindications as well as the timing of various endoscopic interventions. This will help in its safe and effective use and consequently decrease morbidity and mortality from various pancreatic diseases. This review will provide a broad overview of the indications, techniques, and outcomes of pancreatic endotherapy.
Keywords: pancreatitis; endosonography; endoscopic retrograde cholangiopancreatography; stent